CLEAN - Collaborative low-cost environmental and air-quality network. (May 2023) - Campo, Fernando; Franco, Davide; de Campos Santos, Felipe; Blanco-Rodríguez, Andy; Garcia-Ramirez, Alejandro Rafael; Ratão, Gabriel; Hoinaski, Leonardo
Abstract: Air quality monitoring is insufficient in most countries, even though air pollution is a major environmental threat to human health. This paper presents the Collaborative Low-cost Environmental Air-quality Network (CLEAN), which consists of a series of guides and tools to develop the hardware and software for building a network of low-cost air quality monitors. Our web platform provides an Application Programming Interface (API) that allows developers to send the data from their devices to a remote server. All data will be available for any user and data consumers. Collaborators can replicate hardware and firmware components and contribute to the network. We present the hardware prototypes for demonstration, providing the developed firmware and libraries based on the Arduino framework. All guides and documentation for contributing to the initiative are freely available. CLEAN can be a foundation for building knowledge about air quality issues from a local to global scale and serve for educational purposes. Highlights: We present the Collaborative Low-cost Environmental and Air-quality Network – CLEAN. We demonstrate how to build a low-cost air quality monitor and its firmware components. CLEAN has a web application for receiving and organizing the data from monitors. We provide a guide demonstrating how to collaborate and join the network. Joining CLEAN would provide air quality information where data is scarce.